Study Performance Bird Quail Egg Layers ( Coturnix Japonica ) Given Organic Supplements Liquid Gdm In Feed With Different Doses - Marselinus Ndilu; Umi Kalsum; Usman Ali (UNIVERSITAS ISLAM LAMONGAN, 2026)
This study aims to analyze the effect of GDM Liquid Organic Supplement (SOC) in feed on the performance of laying quail (Coturnix japonica). The parameters observed include Hen Day Production (HDP), egg mass, feed conversion, and mortality. The study was conducted for 30 days using 400 6-month-old female laying quails. The research method used a Completely Randomized Design (CRD) with five treatments and four replications. The treatments consisted of P0 (without SOC), P1 (SOC 0.1 % ), P2 (SOC 0.3%), P3 (SOC 0.5%), and P4 (SOC 0.7%). Data were analyzed using analysis of variance (ANOVA) and continued with the Duncan Multiple Range Test (DMRT). The results showed that SOC administration had a significant effect (P <0.05 ) on all observed parameters. Treatment P4 ( 0.7 %) produced the best performance with a HDP value of 98.02%, an egg mass of 12.74 grams, and the lowest feed conversion of 1.66. In addition, the provision of SOC was able to reduce the mortality rate compared to the control treatment. The increase in performance is thought to be caused by the content of probiotic bacteria in SOC which is able to improve the balance of digestive tract microflora, increase nutrient digestibility, and improve feed utilization efficiency. Based on the results of the study, it can be concluded that the use of GDM Liquid Organic Supplement at a dose of 0.5–0.7 % in feed can increase productivity and feed efficiency and reduce mortality in laying quail.